Schwann Cell Migration Induced by Earthworm Extract via Activation of PAs and MMP2/9 Mediated through ERK1/2 and p38. (4th January 2011) - Chang, Yung-Ming; Shih, Ying-Ting; Chen, Yueh-Sheng; Liu, Chien-Liang; Fang, Wen-Kuei; Tsai, Chang-Hai; Tsai, Fuu-Jen; Kuo, Wei-Wen; Lai, Tung-Yuan; Huang, Chih-Yang
Abstract : The earthworm, which has stasis removal and wound-healing functions, is a widely used Chinese herbal medicine in China. Schwann cell migration is critical for the regeneration of injured nerves. Schwann cells provide an essentially supportive activity for neuron regeneration. However, the molecular migration mechanisms induced by earthworms in Schwann cells remain unclear. Here, we investigate the roles of MAPK (ERK1/2, JNK and p38) pathways for earthworm-induced matrix-degrading proteolytic enzyme (PAs and MMP2/9) production in Schwann cells. Moreover, earthworm induced phosphorylation of ERK1/2 and p38, but not JNK, activate the downstream signaling expression of PAs and MMPs in a time-dependent manner. Earthworm-stimulated ERK1/2 and p38 phosphorylation was attenuated by pretreatment with U0126 and SB203580, resulting in migration and uPA-related signal pathway inhibition. The results were confirmed using small interfering ERK1/2 and p38 RNA. These results demonstrated that earthworms can stimulate Schwann cell migration and up-regulate PAs and MMP2/9 expression mediated through the MAPK pathways, ERK1/2 and p38. Taken together, our data suggests the MAPKs (ERK1/2, p38)-, PAs (uPA, tPA)-, MMP (MMP2, MMP9) signaling pathway of Schwann cells regulated by earthworms might play a major role in Schwann cell migration and nerve regeneration.